Daratumumab in untreated newly diagnosed multiple myeloma - Abdallah, Nadine (Ther Adv Hematol, 2019)
The treatment of multiple myeloma has evolved markedly in the last decade, but mortality remains high, emphasizing the need for more effective therapies. Daratumumab, a fully human monoclonal antibody targeting CD38, has shown clinical efficacy in relapsed/refractory multiple myeloma both as monotherapy and in combination with other drugs, including novel agents. More recently, promising results have been reported in patients with untreated newly diagnosed multiple myeloma (NDMM). Clinical trials thus far have shown enhanced efficacy and tolerability of several daratumumab-based combinations in both transplant ineligible and eligible patients, without compromising transplant ability. However, benefit in high-risk subpopulations is still unclear. A subcutaneous formulation of daratumumab has been introduced to decrease the risk of infusion reactions, with preliminary results showing non-inferior efficacy. The antimyeloma activity of daratumumab is achieved through multiple mechanisms including direct, Fc-dependent, and immunomodulatory mechanisms. Enhanced efficacy of daratumumab in combination with immunomodulatory drugs and proteasome inhibitors is supported by preclinical data showing synergism. This review will focus on the role of daratumumab in untreated NDMM patients, highlighting the results of major clinical trials, and listing ongoing trials that are evaluating various daratumumab-based combinations in this setting.